Valine-Glutamine Proteins in Plant Responses to Oxygen and Nitric Oxide - León, José; Gayubas, Beatriz; Castillo, Mari-Cruz (Frontiers in Plant Science, 2021)
Multigene families coding for VQ proteins have been recently identified in all kind of plants but chlorophytes. VQ proteins regulate plant growth and vegetative development, developmental transitions spanning all over the plant life cycle, and responses to biotic and abiotic stresses. VQ proteins have been characterized as transcriptional regulators, which often interact with WRKY transcription factors to regulate gene expression. The regulatory functions exerted by VQ-WRKY complexes on developmental and stress-related responses are sometimes modulated by reversible phosphorylation. Different VQ-WRKY complexes regulate defense against varied pathogens as well as responses to osmotic stress and extreme temperatures. However, despite these well-known functions, new regulatory activities for VQ proteins are still to be explored. Searching public Arabidopsis thaliana transcriptome data for new potential targets of VQ-WRKY regulation allowed us identifying that several VQ protein and WRKY factor encoding genes were differentially expressed in oxygen-related processes such as responses to hypoxia or ozone-triggered oxidative stress. Moreover, some of those were also differentially regulated upon nitric oxide (NO) treatment. These subsets of VQ and WRKY proteins might combine into different VQ-WRKY complexes, thus representing a potential regulatory core of NO- and O2-modulated responses.